TO THE ISSUE OF FORMING THE CONTENT OF TEACHING ENGLISH AS A FOREIGN LANGUAGE: NATIVE ENGLISH VS ENGLISH AS LINGUA FRANCA - Tatiana Lomteva; Inna Reshetova (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the issues of forming the content of English language teaching in the globalization age, when knowledge of the foreign language as a means of communication between non-native speakers belonging to different cultural societies becomes a necessary condition of existence in modern society. That explains the relevance of teaching English as Lingua Franca. In this capacity it doesn t perform ethnic and cultural functions and is not a reflection of Anglo-Saxon mentality.